2014
DOI: 10.1177/1043659614524789
|View full text |Cite
|
Sign up to set email alerts
|

Urban American Indian Adolescent Girls

Abstract: Purpose American Indian (AI) adolescent girls have higher rates of sexual activity, births and STIs compared to the national average. The purpose of this study was to explore factors that influence urban adolescent AI girls' sexual risk behavior (SRB). Design A qualitative study was conducted using grounded theory methodology to reveal factors and processes that influence SRB. Methods Talking circles, individual interviews, and event history calendars were used with 20 urban AI 15-19 year old girls to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The SREHC is written at a 5 th grade reading level and includes open-ended questions, making it appropriate to a diverse range of individuals based on education, socioeconomic status, sexual identity, and location (Flesch, 1948; Kincaid, Fishburne, Robers, & Chisson, 1975). In previous research, it has generated quality data about activities, behavior, events, and transitions occurring over extensive time periods with youth from diverse racial and ethnic backgrounds (Fava et al, 2016; Martyn & Martin, 2003; Martyn, Reifsnider & Murray, 2006; Saftner, Martyn, Momper, Kane Low, & Loveland-Cherry, 2015). …”
Section: Sexual Risk Assessmentmentioning
confidence: 99%
“…The SREHC is written at a 5 th grade reading level and includes open-ended questions, making it appropriate to a diverse range of individuals based on education, socioeconomic status, sexual identity, and location (Flesch, 1948; Kincaid, Fishburne, Robers, & Chisson, 1975). In previous research, it has generated quality data about activities, behavior, events, and transitions occurring over extensive time periods with youth from diverse racial and ethnic backgrounds (Fava et al, 2016; Martyn & Martin, 2003; Martyn, Reifsnider & Murray, 2006; Saftner, Martyn, Momper, Kane Low, & Loveland-Cherry, 2015). …”
Section: Sexual Risk Assessmentmentioning
confidence: 99%
“…While the same gender norms and expectations, such as chastity, modesty (Yosef, 2008), and commitment to family relationships (Al-Krenawi & Graham, 2000) can be barriers to accessing family planning and sexual health resources for Arab-American womenthey may also influence their decision to remain abstinent before marriage thus decreasing their risk of contracting a sexually transmitted infection (STI) or having an unplanned pregnancy. Indeed, researchers have found that modesty and duty to family promote abstinence before marriage among adolescent girls and young women (Martyn, Reifsnider, Barry, Treviño, & Murray, 2006) and extended family connections and responsibility to one's family can be protective against sexual and other risk behaviors (Martyn et al, 2006; Saftner, Martyn, Momper, Kane Low, & Loveland-Cherry, 2014). …”
Section: The Influence Of Arab-american Culture and Societal Normsmentioning
confidence: 99%
“…The secondary analysis findings I present in this article are the result of a larger grounded theory study focused on the development of a theoretical model to understand urban adolescent AI girls’ sexual risk behavior (Saftner, Martyn, Momper, Loveland-Cherry, & Low, 2015). …”
Section: Aimmentioning
confidence: 99%